Student and staff mobility across Europe: From Erasmus to Tempus - Proença, Alberto J. (Zielona Góra: Uniwersytet Zielonogórski)
1794 inter-university cooperation programmes (ICPs) have been funded in 1991/92 under ERASMUS, (European Community Action Scheme for the Mobility of University Students, an European Community (EC) program. From these, 85 contracts lie in the main subject area of Engineering, Technology, Informatics or Computer Science, and 15 of them include both a student and a teaching staff mobility program among 3.9 countries on average. The Dep. of Informatics of University of Minho is leading an ERASMUS ICP since 1989 with 4 participating institutions from 2 countries (P and UK).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka